Qualitative Evaluation of Divergent Thinking in Patients with Schizophrenia - Takahiro Nemoto; Masafumi Mizuno; Haruo Kashima (Behavioural Neurology)
Patients with schizophrenia show deficits across a broad spectrum of neurocognitive domains. In particular, deficits in verbal fluency are common. Verbal fluency tests are neuropsychological tests that assess frontal lobe function or executive function but also assess divergent thinking. However, few studies have considered the impairment of verbal fluency from the viewpoint of divergent thinking. To consider the structure of divergent thinking, not only verbal assessments but also non-verbal assessments are indispensable. We administered several fluency tests, the idea fluency test, the design fluency test, and word (letter and category) fluency tests to 26 patients with schizophrenia and 26 healthy control subjects to evaluate divergent thinking in both groups and assessed their responses qualitatively. An acceptable minimal level of intelligence was maintained in the patient group. Although attention and executive functioning were relatively preserved in the subjects with schizophrenia, they demonstrated significant deficits in divergent thinking and had particular difficulty in producing ideas and designs requiring concept flexibility, a conversion of viewpoint, originality, or novelty. Research on deficits in divergent thinking in patients with schizophrenia may contribute to the development of cognitive and behavioral rehabilitation programs.